Pelatihan Manajemen Pemasaran Telur Bebek Di Desa Sebalik - Rosita Rosita; Jusmawi Bustan; Fetty Maretha; Rini Rini; Silvana Oktanisa; Heni Yuvita; Sari Lestari Zainal Ridho (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Sebalik village is a village located in a water area with the potential to raise laying ducks. In fact, selling duck eggs has quite a high potential for interest because they have a lot of nutrition and fresh duck eggs are rarely found in many places, unlike chicken eggs. On the other hand, for egg-laying duck breeders, marketing and distribution of duck eggs is still an obstacle in egg-laying duck farming because if they are not sold, egg-laying duck breeders cannot generate additional income to support the family economy. From the results of the interviewed it was discovered that laying duck breeders did not know about marketing management as evidenced by the lack of knowledge regarding brands, sales distribution channels and other management functions in marketing. For this reason, marketing management training is carried out. The training was held for one day with 30 participants. From the results of this training, laying duck breeders gained knowledge regarding marketing management and continued with discussions by deepening the obstacles faced when marketing duck eggs by duck egg breeders. Pre-test and post-test were carried out. From the post test results it was found that laying duck breeders already knew and were able to explain marketing management for their duck eggs